HISTORY OF THE STUDY OF THE AVESTA BY ASIAN SCHOLARS - Iskandar Yuldashev (Scholar Express Journal, 2021)
This article highlights Asian researchers' research on the Avesta, as well as how the Avesta data was used in these studies. The research of these scholars is based on the use of Avestan texts, their education, Zoroastrian traditions, information about the way of life, as well as translations of works of foreign scholars. The purpose of this article is to present the scientific work of Asian scientists and their contribution to the scientific analysis of the source
Keywords: Marv; Sughd; Herat; Mallaev